1986
DOI: 10.1007/bf03346944
|View full text |Cite
|
Sign up to set email alerts
|

A rat model of the 131I-induced changes in thyroid function

Abstract: Thyrotoxic patients treated with Iodine-131 (131I) often present with low thyroxine (T4), normal triiodothyronine (T3) and raised thyrotropin (TSH) concentrations in serum. We have developed a rat model of this low T4, raised TSH state. Rats were injected with 50, 150 or 450 mu Ci 131I. A dose of 50 mu Ci 131I caused no significant effect on thyroid function, as assessed by serum parameters whereas both 150 mu Ci and 450 mu Ci 131I caused a significant fall in serum T4 concentration accompanied by a significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 10 publications
1
12
0
Order By: Relevance
“…We found decreased serum www.bjournal.com.br T4 concentrations, while TSH was significantly increased. These findings were in accordance with an earlier report by Reilly et al (16). However, Railly et al showed no change in T3 concentration 85 days after administration of 131 I in their Wistar rat model, our Fisher rat model showed a significant decrease of T3 concentration 3 and 5 months after 131 I administration.…”
Section: Discussionsupporting
confidence: 93%
“…We found decreased serum www.bjournal.com.br T4 concentrations, while TSH was significantly increased. These findings were in accordance with an earlier report by Reilly et al (16). However, Railly et al showed no change in T3 concentration 85 days after administration of 131 I in their Wistar rat model, our Fisher rat model showed a significant decrease of T3 concentration 3 and 5 months after 131 I administration.…”
Section: Discussionsupporting
confidence: 93%
“…The first I-131 dose that we injected into rats was low so as not to effect the thyroid tissue functions, as in the literature. 19 Indeed, the mean injected low dose of I-131 was 51.54 Ϯ 8.6 Ci in our study.…”
Section: Discussionmentioning
confidence: 94%
“…In the same study, the I-131 cleared with a half-life of 3.38 Ϯ 0.61 days. 19 In the light of this previous study, we thought that approximately 50 Ci of I-131 would be suitable for low-dose application. The first I-131 dose that we injected into rats was low so as not to effect the thyroid tissue functions, as in the literature.…”
Section: Discussionmentioning
confidence: 98%
“…131 I is cleared with a half-life of 3.38 Ϯ 0.01 days (Reilly et al, 1986). Taking into account the fact that female rats of this experimental group were exposed to the radioactive iodine no less than twelve days before mating (more than the 10-fold time of effective half-life of the 131 I up to beginning of embryo's thyroid iodine intake), the development of fetuses in this group took place in a state of 131 I-induced maternal hypothyroidism without the influence of direct effects of radioactive iodine.…”
Section: Discussionmentioning
confidence: 99%